f(n)=n+7

Simple and best practice solution for f(n)=n+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(n)=n+7 equation:


Simplifying
f(n) = n + 7

Multiply f * n
fn = n + 7

Reorder the terms:
fn = 7 + n

Solving
fn = 7 + n

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 'n'.
f = 7n-1 + 1

Simplifying
f = 7n-1 + 1

Reorder the terms:
f = 1 + 7n-1

See similar equations:

| 0.8(4x+5)=-3.2 | | 0.375(x+8)=0.75(x+5)+0.125 | | -0.60(n-30)=0.60n-50 | | 2a+6b+8a+5b+7= | | -2-x=-2x+3 | | 950/125 | | 180=6x+12 | | 28x-2y=-32 | | 0.4(4x+9)=18 | | 36x+24y=18 | | 2U+6u+4= | | 3(x-4)+2-4x=-7 | | 2x^2+16+30=0 | | 14-2n=-2 | | y=1/20-6 | | 19=4v-5 | | 1316+188m=0 | | 5x^2=18-27x | | 2w+6=36 | | 3/4g-5=g-5-1/4g | | 4x+17=7x+8 | | 9m+10-14m= | | -3(2x-4)=-2x+8(12-x) | | 2x+129=11x-6 | | -2(-f+11)=-13+2f-9 | | 4y+11=-y+7 | | Lg(3x-5)=3 | | .15*x=298 | | X-51=100 | | 2r^4+46r^2=0 | | (4x+6)*4=88 | | 5+35x=28x+7 |

Equations solver categories